Crystal structure dependent in vitro antioxidant activity of biocompatible calcium gallate MOFs. Issue 15 (30th March 2017) - Hidalgo, Tania; Cooper, Lucy; Gorman, Martin; Lozano-Fernández, Tamara; Simón-Vázquez, Rosana; Mouchaham, Georges; Marrot, Jérome; Guillou, Nathalie; Serre, Christian; Fertey, Pierre; González-Fernández, África; Devic, Thomas; et al.
Abstract : Novel biocompatible Ca-gallate MOFs with progressive release of gallic acid associated with a significant in vitro antioxidant effect. Abstract : Two novel 3-D coordination polymers, denoted MIL-155 and MIL-156 (MIL stands for Materials Institute Lavoisier), built up from calcium and the naturally occurring gallic acid (H4 gal), have been hydrothermally synthesized and their crystal structures were determined by single-crystal X-ray diffraction. These solids are based on different inorganic subunits: infinite chains of edge-sharing dimers of CaO7 polyhedra linked through partially deprotonated gallate ligands (H2 gal 2− ) for MIL-155 or [Ca2 (H2 O)(H2 gal)2 ]·2H2 O, and ribbon-like inorganic subunits containing both eight-fold or six-fold coordinated Ca II ions linked through fully deprotonated gallate ligands (gal 4− ) for MIL-156 or [Ca3 K2 (H2 O)2 (gal)2 ]· n H2 O ( n ∼ 5). Both solids contain small channels filled with water molecules, with, however no accessible porosity towards N2 at 77 K. MIL-155 and MIL-156 were proven to be biocompatible, as evidenced by in vitro assays (viability and cell proliferation/death balance). While the high chemical stability of MIL-156 makes it almost bioinert, the progressive degradation of MIL-155 leads to an important protective antioxidant effect, associated with the release of the bioactive gallate ligand.